Some Convergence Theorems for Contractive Type Mappings in CAT(0) Spaces - Kyung Soo Kim (Abstract and Applied Analysis)
We establish theorems of strong convergence, for the Ishikawa-type (or two step; cf. Ishikawa, 1974) iteration scheme, to a fixed point of a uniformly L-Lipschitzian asymptotically demicontractive mapping and a uniformly L-Lipschitzian hemicontractive mapping in CAT(0) space. Moreover, we will propose some open problems.